2020
DOI: 10.4314/jafs.v18i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the profitability of rice production by credit and non-credit users in Abakaliki Local Government Area of Ebonyi State, Nigeria

Abstract: The study focused on the comparative analysis of the profitability of rice production by credit and non-credit users in Abakaliki Local Government Area of Ebonyi state. The specific objectives of the study were to; determine the socio-economic characteristics of rice farmers in the study area, analyse the factors influencing the output of rice farmers, compare the profitability of rice production by credit and non-credit users and to identify the constraints militating against rice production in the study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…This is consistent with apriori assumptions that more skilled farmers should produce more than those with less or no experience. This result follows the same path with Uhuegbulem et al (2020), who found that farming experience had a substantial impact on the output of rice crop in the Nigerian state of Ebonyi. However, this finding goes against Osanyinlusi and Adenegan's (2016) who reported that production was inversely correlated with farming experience.…”
Section: Factors Affecting Net Production Income Of Rice Farmerssupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with apriori assumptions that more skilled farmers should produce more than those with less or no experience. This result follows the same path with Uhuegbulem et al (2020), who found that farming experience had a substantial impact on the output of rice crop in the Nigerian state of Ebonyi. However, this finding goes against Osanyinlusi and Adenegan's (2016) who reported that production was inversely correlated with farming experience.…”
Section: Factors Affecting Net Production Income Of Rice Farmerssupporting
confidence: 83%
“…This may be explained to mean that there is higher tendency of adopting better agricultural methods if the farmers acquire higher levels of education, which would increase output and consequently higher income. This result shares semblance with that of Uhuegbulem et al. (2020), who also found a strong connection between level of education and yield/output.…”
Section: Factors Affecting Net Production Income Of Rice Farmerssupporting
confidence: 82%